Catalyst for olefin polymerization and preparation method and application thereof
By using catalyst system and spray drying technology with components such as inorganic oxide support in ethylene polymerization catalysts, the problems of low catalyst activity and unsatisfactory polymer form are solved, and efficient, uniform and transparent polymer production is achieved.
Patent Information
- Application Number
- CN202111252268.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-10-27
AI Technical Summary
In industrial applications, existing ethylene polymerization catalysts have problems such as low catalytic activity, poor polymer particle morphology, poor fluidity and wide molecular weight distribution, which are difficult to meet the demand for efficient, uniform and transparent polymers in industrial production.
A catalyst system including inorganic oxide support, magnesium compounds, titanium oxide compounds, organic epoxy compounds, ether compounds and halogenation reagents is adopted to prepare the catalyst through spray drying technology, avoiding the use of a large amount of titanium tetrachloride, ensuring that the catalyst particles are spherical in shape and have low adhesion.
It has achieved the effect of improving catalyst activity, good fluidity of polymer powder, high bulk density and narrow molecular weight distribution, meeting the industry's demand for high-efficiency polymers, and simplifying the preparation process and reducing environmental pollution.
Smart Images

Figure BDA0003322782890000141 
Figure HDA0003322782900000011 
Figure HDA0003322782900000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ethylene polymerization, and in particular relates to a catalyst for olefin polymerization and a preparation method and application thereof. Background Art
[0002] With the development of ethylene polymerization process, the catalyst preparation technology matching the polymerization process is also constantly improving. At present, the Ziegler-Natta catalyst system of Ti / Mg composite still occupies a dominant position in the industrial production of polyethylene. Its main technical indicators include the polymerization activity of the catalyst, hydrogen adjustment sensitivity, copolymerization performance, catalyst particle morphology and particle size distribution. The improvement of catalyst activity and productivity can improve economic benefits. The increase of industrial polymer bulk density allows longer catalyst residence time, which is conducive to increasing reactor output and achieving better reactor operability. Catalyst morphology affects parameters such as bulk density, fluidity, and particle adhesion of polymer powder. The polymer replicates the morphology of the catalyst. Poor catalyst morphology may cause the polymer morphology to deteriorate, which may cause scaling or flaking in industrial equipment. Therefore, the industry needs a catalyst with good morphology control, required particle size and morphology, narrow distribution, high bulk density and low adhesion.
[0003] In addition, Ziegler-Natta catalysts usually have multiple types of active centers, and the molecular weight distribution of the prepared polyethylene resin is relatively wide. Under the condition of a certain polymer molecular weight, if the polymer molecular weight distribution can be narrowed, the comonomer distribution will be more uniform, and the transparency of the film product will be better. When the average molecular weight of the resin is the same, the narrower the molecular weight distribution, the higher the impact strength of the product. Generally, the molecular weight distribution of the resin is changed by changing the process flow or the catalyst system in industry. The method of changing the production process to control the molecular weight distribution of the product is limited by the process. Changing the type and state of the catalyst is an effective way to control the molecular weight distribution.
[0004] At present, the preparation methods of olefin polymerization catalysts mainly include the following: (1) loading method, loading the active center on a preformed inorganic inert carrier such as magnesium chloride, silica gel, aluminum oxide, etc., which can obtain a catalyst with uniform particles and good particle morphology, but the catalyst activity is low. (2) dissolution and precipitation preparation method, which is to dissolve the magnesium compound or the complex of the magnesium compound and then re-precipitate, control certain generation conditions, and prepare a spherical Ti-MgCl2 catalyst, such as Chinese patents CN1158136A, CN1958620A, CN1229092A, CN1299375A, CN1795213A, U.S. Patents US3787384A, US4148754A, US4173547A, US4508843A, but the catalyst particle morphology obtained in this method is not ideal, the distribution is wide or even multi-peak distribution, which is not conducive to the long-term stable operation of the polymerization device. In patent CN1229092A, since organic substances such as phthalic anhydride are used as precipitation aids to promote the precipitation of precipitation when synthesizing the catalyst, and a large amount of titanium tetrachloride needs to be added, not only the presence of anhydride will have an adverse effect on the catalyst, but also the use of a large amount of titanium tetrachloride will cause waste and pollution. At the same time, this system is also easy to become sticky, and the catalyst is difficult to prepare. Chinese patent CN1958620A uses magnesium chloride as a carrier and titanium tetrachloride as an active component. The preparation method of the catalyst is as follows: first dissolve MgCl2 in a solvent system to form a uniform transparent solution, then react with TiCl4 in the presence of a silicone ester compound at low temperature, and precipitate a solid catalyst by slowly heating. When the prepared catalyst component is used for ethylene polymerization, the catalytic activity of the catalyst is relatively high, but due to its unsatisfactory polymer particle morphology, especially the unsatisfactory fluidity of the prepared polymer powder, it still cannot fully meet the needs of industrial production when producing some resins with high requirements for polymer powder fluidity. (3) Inorganic substances such as silica gel with extremely small average particle size are used together with the catalyst active component for spray drying to prepare the catalyst. For example, patents US7276566, US7160833, US6982237, US6806221, etc., and CN1085915A disclose a method for preparing a Ziegler-Natta catalyst system. In tetrahydrofuran, titanium tetrachloride is reduced by magnesium metal to obtain a tetrahydrofuran solution of TiCl3, and then magnesium chloride is dissolved in tetrahydrofuran. The two solutions are fully mixed, unreacted magnesium and undissolved magnesium chloride are filtered out, and the filtered solution is fully mixed with silica gel, and then spray-dried to obtain dispersed particles of the catalyst. The catalyst has high activity and high titanium content. The preparation method requires a filtering step, produces more waste residue, and increases the post-processing steps and costs.
[0005] Therefore, it is necessary to provide a catalyst suitable for ethylene polymerization process, which not only needs to have high catalytic activity and good hydrogen adjustment sensitivity, but also should have good catalyst particle morphology and polymer particle morphology, especially the prepared polymer powder has good fluidity. Summary of the invention
[0006] In order to overcome the problems existing in the prior art, the present invention provides a catalyst for olefin polymerization and a preparation method and application thereof, which has high catalytic activity when used for ethylene homopolymerization or copolymerization, and the prepared polymer powder has good fluidity, high bulk density, and narrow polymer molecular weight distribution. The present invention avoids the use of a large amount of titanium tetrachloride, the catalyst preparation system is not sticky, the obtained catalyst particles are spherical in shape, and the catalyst particles have low adhesion.
[0007] One of the objects of the present invention is to provide a catalyst for olefin polymerization, comprising a mixture and / or reaction product of the following components: an inorganic oxide support, a magnesium compound, an oxygen-containing titanium compound, an organic epoxy compound, an ether compound and a halogenating agent.
[0008] In a preferred embodiment, the inorganic oxide carrier is gas-phase hydrophobic nano-silica.
[0009] In a further preferred embodiment, the particle size of the gas phase hydrophobic nano-silica is 0.01-10 μm, preferably 0.01-2 μm, more preferably 0.01-1 μm, for example, 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0010] The fumed hydrophobic silica is inert to the active components of the catalyst system. The silica can keep the slurry at an appropriate viscosity and endow the spray particles with a certain strength.
[0011] In a preferred embodiment, the magnesium compound is selected from the formula Mg(OR 1 ) m X 1 2-m One or more of the compounds shown, wherein R 1 Selected from C2~C 20 Hydrocarbon or C3~C 20 The cycloalkyl group, X 1 Selected from halogen, 0≤m≤2.
[0012] Among them, the C2~C 20 The hydrocarbon group is a saturated or unsaturated, straight chain or branched hydrocarbon group, and the C3~C 20The cyclic hydrocarbon group is a saturated or unsaturated cyclic hydrocarbon group.
[0013] In a further preferred embodiment, in the formula Mg(OR 1 ) m X 1 2-m In, R 1 C2~C 10 The alkyl group, X 1 is the chlorine element, 0≤m≤2.
[0014] In a further preferred embodiment, the magnesium compound is selected from at least one of diethoxymagnesium, dipropoxymagnesium, dibutoxymagnesium, dioctyloxymagnesium and magnesium dichloride.
[0015] In a preferred embodiment, the oxygen-containing titanium compound is selected from the formula Ti(OR 2 ) n X 2 4-n One or more of the compounds shown, wherein R 2 Selected from C2~C 20 Hydrocarbon or C3~C 20 The cycloalkyl group, X 2 Selected from halogen, 0<n≤4;
[0016] Among them, C2~C 20 The hydrocarbon group is a saturated or unsaturated straight chain or branched hydrocarbon group, C3~C 20 The cyclic hydrocarbon group is a saturated or unsaturated cyclic hydrocarbon group.
[0017] In a further preferred embodiment, in the formula Ti(OR 2 ) n X 2 4-n In, R 2 C2~C 10 The alkyl group, X 2 is the chlorine element, 0<n≤4.
[0018] In a further preferred embodiment, the oxygen-containing titanium compound is at least one selected from tetrabutyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, and tetra-tert-butyl titanate.
[0019] In a preferred embodiment, the organic epoxy compound is selected from one or more of alkylene oxides, halogen-substituted alkylene oxides, olefin-substituted alkylene oxides, diene diepoxides, and glycidyl ethers.
[0020] In a further preferred embodiment, the organic epoxy compound is selected from one or more of ethylene oxide, propylene oxide, butylene oxide, butadiene monoepoxide, butadiene diepoxide, epichlorohydrin, methyl glycidyl ether, and diglycidyl ether.
[0021] In a further more preferred embodiment, the organic epoxy compound is selected from one or more of epichlorohydrin and methyl glycidyl ether.
[0022] In a preferred embodiment, the ether compound is selected from one or more of C2-C20 straight-chain or branched alkyl ethers and C3-C10 cyclic ethers.
[0023] In a further preferred embodiment, the ether compound is selected from one or more of anisole, phenethyl ether, propyl ether, butyl ether, isopropyl ether, isobutyl ether, isopentyl ether, pentyl ether, 1,4-dioxane, tetrahydrofuran, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, cis-2,3-butylene oxide, trans-2,3-butylene oxide, and 9,9-(bismethoxymethyl)fluorene.
[0024] In a further preferred embodiment, the ether compound is selected from C3-C10 cyclic ethers (preferably C3-C5 cyclic ethers), such as tetrahydrofuran and methyltetrahydrofuran.
[0025] In a preferred embodiment, the halogenating agent is selected from R 3 a MX 3 b At least one of the compounds shown, wherein M is selected from one of the third, fourth, and fifth main group elements or transition metal elements, and X 3 Selected from halogen, R 3 Selected from C2~C 20 Hydrocarbon, C2~C 20 Hydroxyl, C3~C 20 Cyclic hydrocarbon groups, C3~C 20 Cycloalkyloxy, C6~C 20 One of the aromatic groups of , a=0, 1, 2 or 3, b=1, 2, 3 or 4.
[0026] Among them, C2~C 20 The hydrocarbon group is C2~C 20 Saturated or unsaturated, straight chain or branched hydrocarbon group, C3~C 20 The cyclic hydrocarbon group is C3~C 20 A saturated or unsaturated cyclic hydrocarbon group.
[0027] In a further preferred embodiment, in R 3 a MX3 b Wherein, M is selected from aluminum or silicon, R 3 Selected from C2~C 10 Hydrocarbon, C3~C 10 One of the cyclic hydrocarbon groups, X 3 Selected from chlorine element, a=0, 1, 2 or 3, b=1, 2, 3 or 4.
[0028] In a further preferred embodiment, the halogenating agent is selected from R 4 A SiCl 4-A , R 4 B AlCl 3-B At least one of the following, where R 4 Selected from C2~C 20 Hydrocarbon, C2~C 20 Hydroxyl, C3~C 20 Cyclic hydrocarbon groups, C3~C 20 Cycloalkyloxy, C6~C 20 One of the aromatic groups, n is an integer, 0≤A<4, 0≤B<3;
[0029] Preferably, the halogenating agent is selected from at least one of ethylaluminum dichloride, diethylaluminum monochloride, isobutylaluminum dichloride, diisobutylaluminum monochloride, isopropylaluminum dichloride, diisopropylaluminum monochloride, silicon tetrachloride, ethoxyaluminum dichloride, phenylaluminum dichloride, and phenoxyaluminum dichloride. Preferably, at least one of diethylaluminum monochloride, isobutylaluminum dichloride, silicon tetrachloride, ethoxyaluminum dichloride, phenylaluminum dichloride, and phenoxyaluminum dichloride is selected.
[0030] In a preferred embodiment, the amount of the oxygen-containing titanium compound is 0.1 to 20 moles per mole of magnesium in the magnesium compound, and / or the amount of the organic epoxy compound is 0.1 to 10 moles, and / or the amount of the ether compound is 0.01 to 100 moles, and / or the amount of the halogenating agent is 0.1 to 50 moles.
[0031] In a further preferred embodiment, the amount of the oxygen-containing titanium compound is 0.1 to 5.0 moles per mole of magnesium in the magnesium compound, and / or the amount of the organic epoxy compound is 0.1 to 5.0 moles, and / or the amount of the ether compound is 5 to 80 moles, and / or the amount of the halogenating agent is 0.1 to 10 moles.
[0032] In a further preferred embodiment, based on each mole of magnesium in the magnesium compound, the amount of the oxygen-containing titanium compound is 0.1 to 3.0 moles, the amount of the organic epoxy compound is 0.1 to 3.0 moles, the amount of the ether compound is 15 to 60 moles, and the amount of the halogenating agent is 0.1 to 5 moles.
[0033] For example, based on each mole of magnesium in the magnesium compound, the amount of the oxygen-containing titanium compound is 0.1, 0.5, 1, 1.5, 2, 2.5 or 3 moles, the amount of the organic epoxy compound is 0.1, 0.5, 1, 1.5, 2, 2.5 or 3 moles, the amount of the ether compound is 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60 moles, and the amount of the halogenating agent is 0.1, 0.2, 0.5, 0.8, 1, 2, 3, 4 or 5 moles.
[0034] Based on each gram of magnesium element in the magnesium compound, the weight of the inorganic oxide support is 1-50g, preferably 2-20g, for example, 1g, 2g, 3g, 4g, 5g, 6g, 7g, 8g, 9g, 10g, 12g, 14g, 16g, 18g, 20g, 25g, 30g, 35g, 40g, 45g or 50g.
[0035] The second object of the present invention is to provide a method for preparing an olefin polymerization catalyst, preferably for preparing the olefin polymerization catalyst composition described in one of the objects of the present invention, the preparation method comprising:
[0036] (1) mixing a magnesium compound, an oxygen-containing titanium compound, an organic epoxy compound and the ether compound, and reacting to obtain a solution 1;
[0037] (2) adding an inorganic oxide carrier to the solution 1 to obtain a suspension;
[0038] (3) adding a halogenating agent to the suspension to obtain a spray masterbatch through reaction;
[0039] (4) spray drying to obtain the catalyst composition.
[0040] In a preferred embodiment, the reaction temperature in step (1) is 30 to 100° C., preferably 40 to 80° C.; more preferably, the reaction is carried out until a transparent solution is obtained, for example, for 1 to 20 hours, preferably 2 to 10 hours.
[0041] Wherein, step (1) is carried out at 30-100°C, preferably 40-80°C, until a transparent solution is obtained. For example, the reaction temperature of step (1) is 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C.
[0042] In a preferred embodiment, step (2) is carried out at 0-100°C for 0.5-10 hours, preferably at 0-80°C for 0.5-4 hours.
[0043] For example, step (2) is carried out at 0°C, 10°C, 20°C, 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C (e.g., room temperature) for 0.5 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.
[0044] In a preferred embodiment, in step (3), the reaction temperature is 0 to 80° C., preferably 20 to 70° C.; and / or the reaction time is 1 min to 10 h, preferably 0.5 to 5 h.
[0045] For example, in step (3), the reaction temperature is 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C; and / or the reaction time is 1 min, 10 min, 30 min, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0046] Among them, in this step, the chlorination reaction or chlorination reduction reaction of the magnesium-titanium complex is completed, that is, the chlorine element replaces the alkoxy group in the magnesium-titanium complex. At the same time, different halogenating agents can also reduce the valence state of the oxygen-containing titanium compound to a lower valence state. The halogenation reaction usually controls the kettle temperature so as not to cause local overheating of the reaction. Stirring is usually performed during the addition process to facilitate the smooth progress of the reaction.
[0047] In a preferred embodiment, in step (4), the spray drying conditions include: an inlet temperature of 100-200°C, preferably 120-160°C; an outlet temperature of 60-130°C, preferably 90-115°C.
[0048] The third object of the present invention is to provide a catalyst obtained by the preparation method described in the second object of the present invention.
[0049] A fourth object of the present invention is to provide a catalyst composition for olefin polymerization, comprising the catalyst described in the first object or the third object of the present invention and an organic aluminum compound.
[0050] In a preferred embodiment, the organoaluminum compound is selected from the formula AlR p X 3-p At least one of the compounds shown, wherein R is selected from one of hydrogen and C1-C20 hydrocarbon groups, X is selected from halogen, and p is selected from an integer of 1-3.
[0051] In a further preferred embodiment, the organoaluminum compound is selected from AlEt3, Al(iso-Bu)3, Al(n-C6H 13 )3. Al(n-C8H 17 )3 and at least one of AlEt2Cl.
[0052] In a further preferred embodiment, the molar ratio of aluminum in the organoaluminum compound to titanium in the catalyst is the conventional aluminum-titanium ratio used in catalysts in the art, preferably 20 to 500, more preferably 30 to 300, for example 20, 30, 50, 80, 100, 150, 200, 250, 300, 400 or 500.
[0053] The fifth object of the present invention is to provide a method for preparing a catalyst composition for olefin polymerization, preferably for preparing the catalyst composition described in the fourth object of the present invention, the preparation method comprising: mixing the catalyst and the organoaluminum compound to obtain the catalyst composition.
[0054] The catalyst and the organoaluminum compound can be directly used in the ethylene polymerization reaction, or the two can be mixed and reacted before being used in the ethylene polymerization reaction.
[0055] The sixth object of the present invention is to provide the use of the catalyst described in the first object of the present invention or the catalyst described in the fourth object of the present invention in olefin polymerization, especially in ethylene homopolymerization or ethylene and α-olefin copolymerization.
[0056] The polymerization reaction conditions are not particularly limited and may be the olefin polymerization conditions commonly used in the art.
[0057] In a preferred embodiment, the α-olefin may be at least one of propylene, butene, pentene, hexene, octene, and 4-methylpentene-1.
[0058] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0059] Compared with the prior art, the present invention has the following beneficial effects: it does not need to use a large amount of titanium tetrachloride, the system is not sticky, the catalyst particles obtained are spherical in shape, the catalyst particles have low adhesion, the preparation process does not require a filtering step, the preparation process is easy to implement, and it is environmentally friendly. When it is used for ethylene homopolymerization or copolymerization, it has high catalytic activity, the prepared polymer powder has good fluidity, the powder obtained by polymerization has a high bulk density, and the molecular weight distribution of the prepared polymer is narrow. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 The scanning electron microscope image of the catalyst obtained in Example 1 is shown.
[0061] Figure 2 The scanning electron microscope image of the catalyst obtained in Comparative Example 1 is shown.
[0062] Figure 3 The scanning electron microscope image of the catalyst obtained in Example 2 is shown.
[0063] Figure 4 The scanning electron microscope image of the catalyst obtained in Example 3 is shown. DETAILED DESCRIPTION
[0064] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0065] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0066] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0067] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0068] Test method:
[0069] Catalyst morphology: measured on an SL-30 field emission environmental scanning electron microscope produced by FEI Company of the United States;
[0070] Polymer molecular weight distribution: The molecular weight distribution (Mw / Mn) of the polyolefin powder was measured using a PL-GPC220 gel permeation chromatograph produced by Polymer Laboratories Ltd., UK, according to the method specified in ASTM D6474-99;
[0071] Catalyst particle size distribution: MASTERSIZE particle size distribution instrument, n-hexane as dispersant, measuring range 0.02-2000μm;
[0072] Melt index: measured using ASTM D1238-99 method;
[0073] Bulk density: measured according to ASTM D1895-69.
[0074] [Example 1]
[0075] (1) Into a glass reactor equipped with a stirring device and purged with N2 and maintained in N2 atmosphere, 42 mmol of magnesium dichloride, 120 ml of tetrahydrofuran, 9.1 mmol of tetrabutyl titanate, and 8.67 mmol of epichlorohydrin were added in sequence, and then the temperature was raised to 70° C. and stirred to react until a transparent solution was formed;
[0076] (2) cooling the transparent solution obtained in step (1) to 50° C., adding 5.6 g of fumed hydrophobic silica (Cabot Corporation TS-610, particle size 0.02-0.1 μm) thereto, stirring and reacting for 2 hours to obtain a suspension;
[0077] (3) adding 12.66 ml of a 30 wt% hexane solution of ethylaluminum dichloride to the suspension obtained in step (2) using a constant pressure dropper. After the addition is complete, stirring and reacting for 1 hour to obtain a slurry to be sprayed;
[0078] (4) Under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was controlled to be 105°C, and the carrier gas flow rate was 30 L / s, and spray drying was performed to obtain a solid flowable powder polyolefin catalyst.
[0079] Catalyst evaluation: 1L hexane, 1mmol triethylaluminum and 20mg of the above catalyst components were added to a 2L stainless steel stirred tank, then the temperature was raised to 75°C, 0.18MPa hydrogen was added, and 0.75MPa ethylene was added after hydrogenation was completed, and the temperature was raised to 85°C for polymerization reaction. After 2 hours of reaction, the addition of ethylene was stopped, the temperature was lowered, the pressure was released, the polyethylene powder was weighed, and the activity of the catalyst was calculated. The bulk density of the polyethylene powder was tested, and the results are shown in Table 1. The results of the catalyst scanning electron microscope test are shown in Figure 1 .
[0080] [Example 2]
[0081] The catalyst component was prepared according to the method of Example 1, except that 5.6 g of AEROSIL R 972, which has a BET range of 90-130 m / s, was used as the fumed hydrophobic nano-silica in step (2). 2 / g.
[0082] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 1. The results of the catalyst scanning electron microscopy test are shown in Figure 3 .
[0083] [Example 3]
[0084] The catalyst component was prepared according to the method of Example 1, except that 5.6 g of AEROSIL R 974, which has a BET range of 150-190 m / s, was used as the fumed hydrophobic nanosilica in step (2). 2 / g.
[0085] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 1. The results of the catalyst scanning electron microscopy test are shown in Figure 4 .
[0086] [Example 4]
[0087] The catalyst component was prepared according to the method of Example 1, except that 9.1 mmol of tetrabutyl titanate in step (1) was replaced by 9.1 mmol of tetraethyl titanate.
[0088] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 1.
[0089] [Example 5]
[0090] The catalyst component was prepared according to the method of Example 1, except that 120 ml of tetrahydrofuran in step (1) was replaced by 135 ml of tetrahydrofuran. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 1.
[0091] [Example 6]
[0092] The catalyst component was prepared according to the method of Example 1, except that 12.66 ml of 30 wt% ethylaluminum dichloride solution in step (3) was replaced by 2.6 ml of silicon tetrachloride. The catalyst was evaluated as in Example 1. The polymerization results are shown in Table 1.
[0093] [Example 7]
[0094] The catalyst component was prepared according to the method of Example 1, except that the tetrabutyl titanate in step (1) was adjusted from 9.1 mmol to 14.6 mmol. The catalyst was evaluated in the same manner as in Example 1, and the polymerization results are shown in Table 1.
[0095] [Example 8]
[0096] The catalyst component was prepared according to the method of Example 1, except that the epichlorohydrin in step (1) was changed from 8.67 mmol to 10.5 mmol. The catalyst was evaluated in the same manner as in Example 1, and the polymerization results are shown in Table 1.
[0097] [Example 9]
[0098] The catalyst component was prepared according to the method of Example 1, except that the 12.66 ml of 30 wt% ethylaluminum dichloride hexane solution in step (3) was changed to 20 ml. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 1.
[0099] [Example 10]
[0100] The catalyst component was prepared according to the method of Example 1, except that the reaction temperature in step (1) was changed from 70° C. to 60° C. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 1.
[0101] [Comparative Example 1]
[0102] (1) Into a glass reactor equipped with a stirring device and purged with N2 and maintained in N2 atmosphere, 42 mmol of magnesium dichloride, 120 ml of tetrahydrofuran, and 9.1 mmol of titanium tetrachloride were added in sequence, and the temperature was raised to 70°C and stirred for reaction until a transparent solution was formed.
[0103] (2) cooling the transparent solution obtained in step (1) to 50° C., adding 5.6 g of fumed hydrophobic silica (Cabot Corporation TS-610, particle size 0.02-0.1 μm) thereto, stirring and reacting for 2 hours to obtain a suspension;
[0104] (3) Under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was controlled to be 105°C, and the carrier gas flow rate was 30 L / s, and spray drying was performed to obtain a solid flowable powder polyolefin catalyst.
[0105] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 1. The results of the catalyst scanning electron microscopy test are shown in Figure 2 .
[0106] [Comparative Example 2]
[0107] (1) Into a glass reactor equipped with a stirring device and purged with N2 and maintained in N2 atmosphere, 42 mmol of magnesium dichloride, 120 ml of tetrahydrofuran, 9.1 mmol of titanium tetrachloride, and 8.67 mmol of epichlorohydrin were added in sequence, and the temperature was raised to 70°C and stirred to react until a transparent solution was formed.
[0108] (2) cooling the transparent solution obtained in step (1) to 50° C., adding 5.6 g of fumed hydrophobic silica (Cabot Corporation TS-610, particle size 0.02-0.1 μm) thereto, stirring and reacting for 2 hours to obtain a suspension;
[0109] (3) Under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was controlled to be 105°C, and the carrier gas flow rate was 30 L / s, and spray drying was performed to obtain a solid flowable powder polyolefin catalyst.
[0110] The evaluation of the catalyst was the same as in Example 1. The polymerization results are shown in Table 1.
[0111] [Comparative Example 3]
[0112] The catalyst component was prepared according to the method of Example 1, except that 9.1 mmol of titanium tetrachloride was used to replace the ethylaluminum dichloride solution, and other conditions remained unchanged. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 1.
[0113] [Comparative Example 4]
[0114] The catalyst component was prepared according to the method of Example 1, except that 42 mmol of ethylene glycol monobutyl ether was also added in step (1). The catalyst was evaluated in the same manner as in Example 1, and the polymerization results are shown in Table 1.
[0115] [Comparative Example 5]
[0116] The catalyst component was prepared according to the method of Example 1, except that 5.6 g of XFI05 nano-silicon dioxide was used instead of TS610. The evaluation of the catalyst was the same as in Example 1, and the polymerization results are shown in Table 1.
[0117] Table 1
[0118]
[0119] (Wherein: BD-bulk density; PD-molecular weight distribution Mw / Mn)
[0120] It can be seen from the experimental data of the examples and comparative examples in Table 1 that the activity of the catalyst obtained by the present invention is maintained at a high level while the polymer bulk density is high. The polymer molecular weight distribution is narrow, from Figure 1-Figure 4 It can be seen from the comparison that, compared with the comparative example catalyst, the catalyst of the present invention has a quasi-spherical particle shape, uniform particles, less adhesion on the particle surface, good sphericity and good dispersibility.
[0121] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A catalyst for olefin polymerization, comprising a mixture and / or a reaction product of the following components: An inorganic oxide carrier, a magnesium compound, an oxygen-containing titanium compound, an organic epoxy compound, an ether compound and a halogenating agent, wherein the ether compound is selected from one or more of C2-C20 straight-chain or branched alkyl ethers and C3-C10 cyclic ethers.
2. The catalyst according to claim 1, characterized in that The inorganic oxide carrier is gas phase hydrophobic nano-silica.
3. The catalyst according to claim 2, characterized in that The particle size of the gas-phase hydrophobic nano-silicon dioxide is 0.01-10 μm.
4. The catalyst according to claim 2, characterized in that The particle size of the gas-phase hydrophobic nano-silicon dioxide is 0.01-2 μm.
5. The catalyst according to claim 1, characterized in that The magnesium compound is selected from the formula Mg(OR 1 ) m X 1 2-m One or more of the compounds shown, wherein R 1 Selected from C2~C 20 Hydrocarbon or C3~C 20 The cycloalkyl group, X 1 Selected from halogen, 0≤m≤2.
6. The catalyst according to claim 5, characterized in that In the formula Mg(OR 1 ) m X 1 2-m In, R 1 C2~C 10 The alkyl group, X 1 is the chlorine element, 0≤m≤2.
7. The catalyst according to claim 1, characterized in that The oxygen-containing titanium compound is selected from the formula Ti(OR 2 ) n X 2 4-n One or more of the compounds shown, wherein R 2 Selected from C2~C 20 Hydrocarbon or C3~C 20 The cycloalkyl group, X 2 Selected from halogen, 0<n≤4.
8. The catalyst according to claim 7, characterized in that In the formula Ti(OR 2 ) n X 2 4-n In, R 2 C2~C 10 The alkyl group, X 2 is the chlorine element, 0<n≤4.
9. The catalyst according to claim 1, characterized in that The organic epoxy compound is selected from one or more of alkylene oxides, halogen-substituted alkylene oxides, olefin-substituted alkylene oxides, diene diepoxides, and glycidyl ethers; and / or, The ether compound is selected from one or more of anisole, phenethyl ether, propyl ether, butyl ether, isopropyl ether, isobutyl ether, isopentyl ether, pentyl ether, 1,4-dioxane, tetrahydrofuran, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, cis-2,3-butylene oxide, trans-2,3-butylene oxide, and 9,9-(bismethoxymethyl)fluorene.
10. The catalyst according to claim 9, characterized in that The organic epoxy compound is selected from one or more of ethylene oxide, propylene oxide, butylene oxide, butadiene monoepoxide, butadiene diepoxide, epichlorohydrin, methyl glycidyl ether, and diglycidyl ether.
11. The catalyst according to claim 1, characterized in that The halogenating agent is selected from R 3 a MX 3 b At least one of the compounds shown, wherein M is selected from one of the third, fourth, and fifth main group elements or transition metal elements, and X 3 Selected from halogen, R 3 Selected from C2~C 20 Hydrocarbon, C2~C 20 Hydroxyl, C3~C 20 Cyclic hydrocarbon groups, C3~C 20 Cycloalkyloxy, C6~C 20 One of the aromatic groups of , a=0, 1, 2 or 3, b=1, 2, 3 or 4.
12. The catalyst according to claim 11, characterized in that In R 3 a MX 3 b Wherein, M is selected from aluminum or silicon, R 3 Selected from C2~C 10 Hydrocarbon, C3~C 10 One of the cyclic hydrocarbon groups, X 3 Selected from chlorine element, a=0, 1, 2 or 3, b=1, 2, 3 or 4.
13. The catalyst according to any one of claims 1 to 12, characterized in that Based on each mole of magnesium in the magnesium compound, the amount of the oxygen-containing titanium compound is 0.1 to 20 moles, and / or the amount of the organic epoxy compound is 0.1 to 10 moles, and / or the amount of the ether compound is 0.01 to 100 moles, and / or the amount of the halogenating agent is 0.1 to 50 moles.
14. The catalyst according to claim 13, characterized in that The amount of the oxygen-containing titanium compound is 0.1 to 5.0 moles per mole of magnesium in the magnesium compound, and / or the amount of the organic epoxy compound is 0.1 to 5.0 moles, and / or the amount of the ether compound is 5 to 80 moles, and / or the amount of the halogenating agent is 0.1 to 10 moles.
15. The catalyst according to claim 13, characterized in that The weight of the inorganic oxide support is 1-50 g based on gram of magnesium element in the magnesium compound.
16. The catalyst according to claim 15, characterized in that The weight of the inorganic oxide support is 2-20 g based on gram of magnesium element in the magnesium compound.
17. A method for preparing an olefin polymerization catalyst, for preparing the olefin polymerization catalyst composition according to any one of claims 1 to 16, the method comprising: (1) mixing a magnesium compound, an oxygen-containing titanium compound, an organic epoxy compound and the ether compound, and reacting to obtain a solution 1; (2) adding an inorganic oxide carrier to the solution 1 to obtain a suspension; (3) adding a halogenating agent to the suspension to obtain a spray masterbatch through reaction; (4) spray drying to obtain the catalyst composition.
18. The preparation method according to claim 17, characterized in that: The reaction temperature in step (1) is 30-100°C; and / or, Step (2) is performed at 0-100° C. for 0.5-10 hours; and / or, In step (3), the reaction temperature is 0-80°C; and / or the reaction time is 1 min-10 h; and / or, In step (4), the spray drying conditions include: an inlet temperature of 100 to 200°C; and an outlet temperature of 60 to 130°C.
19. The preparation method according to claim 18, characterized in that: The reaction temperature in step (1) is 40-80°C; and / or, Step (2) is carried out at 0-80° C. for 0.5-4 hours; and / or, In step (3), the reaction temperature is 20-70°C; and / or the reaction time is 0.5-5h; and / or, In step (4), the spray drying conditions include: an inlet temperature of 120 to 160°C; and an outlet temperature of 90 to 115°C.
20. A catalyst obtained by the preparation method according to any one of claims 17 to 19.
21. A catalyst composition for olefin polymerization, comprising the catalyst according to any one of claims 1 to 16 or claim 20 and an organic aluminum compound.
22. The catalyst composition for olefin polymerization according to claim 21, characterized in that The organoaluminum compound is selected from the formula AlR p X 3-p At least one of the compounds shown, wherein R is selected from one of hydrogen and C1-C20 hydrocarbon groups, X is selected from halogen, and p is selected from an integer of 1-3.
23. The catalyst composition for olefin polymerization according to claim 21, characterized in that The molar ratio of aluminum in the organic aluminum compound to titanium in the catalyst is 20-500.
24. A method for preparing a catalyst composition for olefin polymerization, for preparing the catalyst composition according to any one of claims 21 to 23, the preparation method comprising: The catalyst and the organoaluminum compound are mixed to obtain the catalyst composition.
25. Use of the catalyst according to any one of claims 1 to 16 or claim 20 or the catalyst composition according to claim 24 in olefin polymerization.
26. The use according to claim 25, characterized in that Application in ethylene homopolymerization or copolymerization of ethylene and other α-olefins.
27. The use according to claim 26, characterized in that The α-olefin is at least one of propylene, butene, pentene, hexene, octene and 4-methylpentene-1.
Citation Information
Patent Citations
Process for producing ethylene polymers having reduced hexane extractable content
CN1085915A
Procatalyst for ethylene polymer production, method for its preparation and use
CN1158136A
Catalyst used for vinyl polymerizing or copolymerizing and its making method
CN1229092A
Olfin polymerization catalyst componnet, its prepn. and use
CN1299375A
Novel polymerisation catalyst
CN1795213A